2018
DOI: 10.1021/acsanm.8b01436
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Hot Spots in Gold Nanostructures on Direct Plasmon-Enhanced Electrochemistry

Abstract: Recently, the direct utilization of plasmonic metal nanostructures in accelerating the electrochemical reactions reveals the importance of hot charge carriers generated by localized surface plasmon resonance (LSPR). However, the effect of morphological forms of the same metal element on direct plasmon-enhanced electrocatalytic activity has not yet been well documented. Herein, four kinds of Au nanostructures with different morphologies of nanospheres (NSPs), nanorods (NRs), nanostars (NSs), and triangular nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…Many configurations and shapes of metal nanoparticles have been fabricated and studied in photocatalysis. [193,[202][203][204][205] Many factors contribute to photocatalytic performance enhancement, including the formation of local electric field, light absorption enhancement due to SPR, and charge carriers generation improvement. [28] In 2018, Jeong et al demonstrated silver nanoparticles embedded in BiVO 4 nanocomposite photoanode to enhance photocatalytic current densities, as shown in Figure 13a.…”
Section: Plasmonic Resonancementioning
confidence: 99%
“…Many configurations and shapes of metal nanoparticles have been fabricated and studied in photocatalysis. [193,[202][203][204][205] Many factors contribute to photocatalytic performance enhancement, including the formation of local electric field, light absorption enhancement due to SPR, and charge carriers generation improvement. [28] In 2018, Jeong et al demonstrated silver nanoparticles embedded in BiVO 4 nanocomposite photoanode to enhance photocatalytic current densities, as shown in Figure 13a.…”
Section: Plasmonic Resonancementioning
confidence: 99%
“…Over the last two decades, a great deal of research has been devoted to the development of nanostructured materials for improved electrocatalysis (Table 1). It is now well established that next to morphology, the size and shape of the nanomaterials are considerably affecting the overall electrocatalytic activity of such systems [5,27]. All of the developed systems focused on electrocatalysis in the dark or under daylight, and a wealth of information on the structure/activity relationship of electrocatalysis on light-induced resonant phenomena have been neglected.…”
Section: Synthesis Of Plasmonic Electrocatalysts: From Single To Mmentioning
confidence: 99%
“…Gold nanoparticles decorating glassy carbon electrodes [4,5] as well as gold nanofiber-based electrodes [11] have been proposed for plasmon-induced electrochemical processes. Wang et al underlined the importance of hot spots in Au NSs on direct plasmon-enhanced electrochemistry using the oxidation of ascorbic acid as a model [5]. He suggested that an increased number of hot spots, as observed on gold nanostars (Au NSs), results in the best plasmon-enhanced electrochemistry effects.…”
Section: Synthesis Of Plasmonic Electrocatalysts: From Single To Mmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Surprisingly, there are only a few reports on plasmon-enhanced electrochemical reactions using the intertwined plasmoncatalytic-electrochemical properties of gold nanostructures. [8][9][10] . Minteer and co-workers fabricated Au nanofiber-based electrode for plasmon-enhanced electrocatalytic oxidation of ethanol and methanol in alkaline media.…”
Section: Introductionmentioning
confidence: 99%